Impact of community based breeding program on breeding buck availability, growth and reproductive performance of Black Bengal goat (Bangladesh Journal of Animal Science, 2020)
The present study was undertaken to evaluate the availability of breeding bucks as well as growth and reproductive performances of Black Bengal goat under community based breeding program. A total of 30 goat rearers in three areas of Sakhipur upazilla were selected based on the survey result. Selected goat rearers were trained on scientific rearing, management and community-based breeding of Black Bengal goat and also build up community link with them. Three Black Bengal breeding bucks have been distributed among three potential farmers in three villages under Sakhipur upazilla. The management and performance of Black Bengal goats were monitored closely and analyze the impact of community based breeding program. The analysis of the growth performance showed that male kids attained significantly (p